2009
DOI: 10.1111/j.1537-2995.2008.02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of recombinant activated Factor VII in patients with massive uncontrolled bleeding: a retrospective observational analysis

Abstract: This study suggests that rFVIIa may play a role in patients with massive uncontrolled blood loss by reducing the amount of RBC and FFP transfusions and by improving the coagulation variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As for rFVIIa dose, among patients with central nervous system bleeding who received rFVIIa, there was a significant correlation between dose and rates of arterial thromboembolic events [22]. Although many publications on off-label use of rFVIIa reported an effective median dose similar to that of standard indications, 90 μg/kg body weight [4,23], or even much higher, up to 200 μg/kg body weight [10], there are some studies indicating a therapeutic effect already at lower doses, in particular in certain indications, such as acute intracerebral haemorrhage [8], traumatic bleeding [11,12], retropubic prostatectomy [15] or cardiac surgery [24,25]. In 2004, we had chosen to employ for off-label use at our institution a low rFVIIa dose of 60 μg/kg because it leads to a plasmatic rFVIIa concentration which still is 5-6 times higher than the minimal effective level [26], and because high rFVIIa doses could theoretically lead to excessive thrombin generation with consecutive activation of the anticoagulant protein C pathway by means of thrombin binding thrombomodulin [27].…”
Section: Introductionmentioning
confidence: 99%
“…As for rFVIIa dose, among patients with central nervous system bleeding who received rFVIIa, there was a significant correlation between dose and rates of arterial thromboembolic events [22]. Although many publications on off-label use of rFVIIa reported an effective median dose similar to that of standard indications, 90 μg/kg body weight [4,23], or even much higher, up to 200 μg/kg body weight [10], there are some studies indicating a therapeutic effect already at lower doses, in particular in certain indications, such as acute intracerebral haemorrhage [8], traumatic bleeding [11,12], retropubic prostatectomy [15] or cardiac surgery [24,25]. In 2004, we had chosen to employ for off-label use at our institution a low rFVIIa dose of 60 μg/kg because it leads to a plasmatic rFVIIa concentration which still is 5-6 times higher than the minimal effective level [26], and because high rFVIIa doses could theoretically lead to excessive thrombin generation with consecutive activation of the anticoagulant protein C pathway by means of thrombin binding thrombomodulin [27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results of our study were in concordance with some other studies in which rFVIIa was used as a prophylactic agent, although none were in redo cardiac surgeries. In addition, as mentioned in other studies, rFVIIa could be used both as a prophylactic agent and as a "rescue therapy" in order to treat refractory bleeding; however, there are some controversies on that regard ( 1 , 5 , 10 , 17 , 18 , 28 , 29 , 34 - 39 ). Gill et al performed a randomized placebo-controlled trial in those with bleeding after cardiac surgery; they observed more critical adverse events in the rFVIIa groups (40 and 80 µg/kg) than in placebo group although it was statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of post-cardiac surgery bleeding can be either surgical or nonsurgical ( 1 - 4 ). Microvascular diffuse bleeding after cardiac surgery is still considered as an important and common problem leading to the use of antifibrinolytic drugs; however, the efficacy of these drugs is not always the same ( 1 - 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some institutions have developed policies and guidelines for rFVIIa use, recommending caution in administering to patients at increased risk for thrombotic complications, ie, history of coronary artery disease, cerebral vascular disease, or venous or arterial thrombosis, DIC, those receiving extracorporeal membrane oxygenation or on ventricular assist device, or following cardiac surgery [34]. Nevertheless, a recent retrospective observational analysis of patients treated with rFVIIa for massive bleeding noted significantly reduced transfusion requirements, improved coagulation variables, and a 56% survival rate [35]. Another study found that treatment with rFVIIa within 4 hours of onset of intracerebral hemorrhage limited growth of the hematoma, reduced mortality, and improved functional outcomes at 90 days, despite a small increase in thromboembolism [36].…”
Section: Intraoperative Techniques To Minimize Blood Lossmentioning
confidence: 97%